Little Mogadishu : Eastleigh, Nairobi's global Somali hub - Carrier, Neil C. M. (New York: Oxford University Press, 2016)
"Nairobi's Eastleigh estate has undergone profound change over the past two decades. Previously a quiet residential zone, the arrival of vast numbers of Somali refugees catalyzed its trans- formation into 'Little Mogadishu', a global hub for Somali business. Dozens of malls and hotels have sprouted from its muddy streets, attracting thousands of shoppers. Nonetheless, despite boosting Kenya's economy, the estate and its residents are held in suspicion over alleged links to Islamic terrorism, especially after the 2013 Westgate Mall attack, while local and international media have suggested with little evidence that its economic boom owes much to capital derived from Indian Ocean piracy. In contrast to such sensationalized reporting, Little Mogadishu is based on detailed historical and ethnographic research and explores the social and historical underpinnings of this economic boom. It examines how transnational networks converged on Eastleigh in the wake of the collapse of the Somali state, attracting capital from the Somali diaspora, and bringing goods--especially clothes and electronics--from Dubai, China and elsewhere that are much in demand in East Africa. In so doing, Little Mogadishu provides a compelling case-study of the developmental impact diasporas and transnational trade can have, albeit in a country where many see this development as suspect."
Introduction: Welcome to Eastleigh -- From Nairobi East to Little Mogadishu -- Urban transformation -- More than Little Mogadishu -- Living the Eastleigh dream -- Trust and the Easleigh entrepreneur -- Demanding goods -- State of suspicion -- Conclusion: Eastleigh and cities yet to come.
Includes bibliographical references (pages 279-301) and index.
Keywords: Terrorism -- Kenya; Eastleigh (Kenya) -- Economic conditions; Kenya -- Commercial policy